FUNGSI IMPLIKATUR DALAM TUTURAN TOKOH NOVEL LE PETIT PRINCE KARYA ANTOINE DE SAINT-EXUPÉRY - Marshawibowo, Difa Shafa; Pujihastuti, Etin; Sholikhati , Nur Indah (Fakultas Ilmu Budaya, Universitas Padjadjaran, 2026)
This study focuses on examining the function of implicature in conversations found in Antoine de Saint-Exupéry's novel Le Petit Prince, using Leech's theory of implicature as its main foundation. Pragmatics, particularly implicature in conversation, is the main focus because it reveals implied meanings that are not explicitly stated by the speaker, while also describing the relationship between context, purpose, and interactions between characters. The novel Le Petit Prince was chosen because of the moral values and symbolism conveyed through simple but meaningful dialogues. Descriptive qualitative methods were used in this study, with observation and recording techniques as a means of collecting data in the form of characters' utterances in the novel. Data analysis was carried out through a process of reduction, presentation, and conclusion drawing, with triangulation as a means of validating the results. The results of the study show that there are 12 implicature functions in the conversations, consisting of 2 assertive functions, 5 directive functions, 2 commissive functions, and 3 expressive functions. The dominance of the directive function in the novel indicates the existence of power dynamics in the relationships between characters, as well as reflecting the social and moral values that the author wants to convey through symbolic dialogue. The findings are expected to provide a deeper understanding of the important role of directive implicatures in character and plot development in novels, as well as their relevance to further research in the fields of literature and pragmatics.